Pengaruh Latihan Resistance Band Dan Latihan Beban Terhadap Hasil Tendangan Dolyo Chagi Pada Savic Taekwondo Klub Bandar Lampung - Ramadhan, Z. Fajar; Sari, F.; Gumay, J. Renaldy (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of resistance band training and weight training (1kg barbell) on the results of dolyo chagi kicks in taekwondo athletes. The method used in this research is an experiment (true experiment) while the research design used is a pre test-post test group design. The population in this study were athletes from the Dojang Savic Taekwondo Club in Bandar Lampung. The total sample used was 24 athletes from the total sample, so this research is called population research which was divided into 2 groups. The data collection technique for kick results uses the dolyo chagi kick instrument. The results of the research show that there is a significant influence from resistance band training which gets a calculated t value of 19.58 > 1.782 and weight training gets a calculated t value of 22.76 > 1.782 which has a significant influence as seen from the calculations. shows t count > t table.